New Population and Range Extension of the Critically Endangered Ecuadorian Brown-Headed Spider Monkey (Ateles Fusciceps Fusciceps) in Western Ecuador. (March 2016) - Cervera, Laura; Griffith, Daniel M.
The western lowlands of Ecuador form part of the Tumbes-Chocó-Magdalena hotspot, a region with exceptionally high endemism but also elevated rates of deforestation. The Critically Endangered Ecuadorian brown-headed spider monkey ( Ateles fusciceps fusciceps ) is endemic to the region and threatened by continuing habitat loss and hunting. Studies of the species' conservation status maintain that its current distribution is restricted to several large tracts of primary forest remaining in northwestern Ecuador, and that the total population numbers around 250 individuals. We report a previously unknown population of brown-headed spider monkeys found 100 km southwest of the species' known distribution in a highly fragmented landscape of Manabí province. This finding not only represents an important advance in our knowledge of the species' geographic distribution, but also suggests that brown-headed spider monkeys may be able to persist as a metapopulation in human-modified landscapes.